Glimpses of The Oral History of Tibetan Studies - Ford, Renée; Griffiths, Rachael; Sehnalova, Anna; Wojahn, Daniel (Buddhist Studies Review, 2021)
The Oral History of Tibetan Studies (OHTS) project collects memories of individuals who have contributed to the formation of Tibetan Studies as an independent academic discipline in the second half of the twentieth century. Through interview recordings, it explores two aspects: the development of the discipline itself, and the distinctive life-stories of the individuals involved. The project includes scholars and academics, Tibetan teachers and traditional scholars, artists, photographers, book publishers, and sponsors. The oral testimonies also provide crucial information on related academic fields, such as Buddhist and Religious Studies, Anthropology, and Asian Studies more generally, and present a kaleidoscope of broader social, cultural, and educational developments. Of particular interest is the interconnection with Buddhist Studies, as exemplified in the UK and through links with the International Association of Buddhist Studies. This report aims to introduce the project, its open access online archive, and future plans.